A Novel Promoter CpG-Based Signature for Long-Term Survival Prediction of Breast Cancer Patients - Guo, Yang; Mao, Xiaoyun; Qiao, Zhen; Chen, Bo; Jin, Feng (Frontiers in Oncology, 2020)
Breast cancer (BC) has become one of the most concerned public health issues in the worldwide, due to the growing incidence, high mortality and huge economic burden. At present, there is a lack of effective methods to predict the long-term survival of BC patients. DNA methylation have been considered to make important effects in cancer development. Since the DNA methylation can be varied with internal and external factors, it has become a research hotspot for investigating the tumorgenesis and cancer development. At the same time, DNA methylation has also been intensively explored as a target for epigenetic treatment. Our study explored a novel promoter CpG-Based signature for long-term survival prediction of BC patients. We used The Cancer Genome Atlas (TCGA) data as training set and results were validated in an independent dataset from Gene Expression Omnibus (GEO). The 10-year Receiver Operating characteristic Curves of Risk score presented an Area Under Curve of over 0.7 for both cohorts. A nomogram was also constructed. The promoter CpG-based signature exhibited good prognostic prediction efficacy in the long-term overall survival of BC patients.